The Scaling and Modeling of Pay and the Robustness of the Effect of Core Self Evaluations on Career Success - Ganzach, Yoav; Pazy, Asya (Frontiers in Psychology, 2021)
A number of recent studies used nominal pay in estimating the effects of individual differences on pay. We show that this practice may lead to results that are substantially different from the results of when the logarithm of pay is used, and that the differences between the two types of models are considerable when it comes to interaction effects, but less so when it comes to main effects. We conduct three constructive replications of previous studies that used either log pay or nominal pay to examine these differences.